1999
DOI: 10.1126/science.283.5404.996
|View full text |Cite
|
Sign up to set email alerts
|

A Copper Cofactor for the Ethylene Receptor ETR1 from Arabidopsis

Abstract: The ETR1 receptor from Arabidopsis binds the gaseous hormone ethylene. A copper ion associated with the ethylene-binding domain is required for high-affinity ethylene-binding activity. A missense mutation in the domain that renders the plant insensitive to ethylene eliminates both ethylene binding and the interaction of copper with the receptor. A sequence from the genome of the cyanobacterium Synechocystis sp. strain 6803 that shows homology to the ethylene-binding domain of ETR1 encodes a functional ethylene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
563
1
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 595 publications
(593 citation statements)
references
References 19 publications
18
563
1
8
Order By: Relevance
“…As previously reported [5], addition of both CuSO 4 and AgNO 3 led to an increase in ethylene binding in ETR1 (Fig. 1).…”
Section: Gold Ions Support High-affinity Ethylene Binding In Etr1supporting
confidence: 87%
See 3 more Smart Citations
“…As previously reported [5], addition of both CuSO 4 and AgNO 3 led to an increase in ethylene binding in ETR1 (Fig. 1).…”
Section: Gold Ions Support High-affinity Ethylene Binding In Etr1supporting
confidence: 87%
“…It has been shown that Cu(I) ions are required for high-affinity ethylene binding in exogenously expressed ETR1 receptors [5] supporting earlier speculations about the requirement for a transition metal cofactor for ethylene binding [7,8]. Additionally, genetic studies indicate that the RAN1 copper transporter acts upstream of the receptors [9,10].…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…The ethylene receptors require the copper ion for high-affinity ethylene binding. 29 Silver can substitute for copper as a cofactor and thereby inhibit ethylene responses. 30 In the presence of STS, wild-type plants showed increased leaf expansion as previously reported.…”
mentioning
confidence: 99%